Evaluation of the novel bipolar vessel sealing and cutting device BiCision® in a porcine model. Issue 6 (November 2012) - Szyrach, Mara Natascha; Paschenda, Pascal; Afify, Mamdouh; Schäller, Daniel; Tolba, René Hany
Abstract Background: Energy-based technologies for tissue sealing and cutting are increasingly supplementing current standards used for haemostasis and dissection during laparoscopic surgery. For their safe and efficacious use in clinical practice, these instruments have to guarantee sufficient burst resistance and low thermal damage to adjacent tissue in combination with good cutting characteristics. Material and methods: The novel laparoscopic, bipolar electrosurgical sealing and cutting instrument BiCision® was compared to a commercially available laparoscopic device (EnSeal™) on visceral and peripheral arteries and veins in an animal model. Results: For all parameters investigated (burst pressure, cut quality, tissue adhering to the instrument, time needed to seal and cut the vessel and thermal damage), BiCision® was at least as good as EnSeal™. Regarding the burst pressure, BiCision® was superior over EnSeal™ in arteries: 600 mmHg (±478) versus 241 (±269) mmHg, respectively (p < 0.0001*). In veins, almost equivalent burst pressures of 155 ± 134 mmHg (BiCision®) and 173 ± 139 mmHg (EnSeal™) were obtained. Conclusion: BiCision® appeared to be as good as or even superior to EnSeal™. Since EnSeal™ has already been shown to be safe and has been successfully used in clinical practice, BiCision® is assumed to be as efficient and reliable as EnSeal™ under pre-clinical conditions.